Social Support, Well-being and Involvement of Fathers in Transnational Families in the Philippines - Garabiles, Melissa R (Archīum Ateneo, 2021)
This study investigated left-behind Filipino fathers and their involvement as child caregivers. It hypothesized that social support and well-being predict paternal involvement, with well-being as the mediator. Results showed that familial and peer support predicted involvement, with well-being as mediator. Spousal support did not predict involvement or well-being. Findings highlight the importance of familial and peer support to left-behind fathers. Interactions between significant predictors of involvement present novel pathways to childcare. The non-significant role of spousal support is discussed in the context of transnational migration. Several interventions involving families and peers are suggested.